Non-Aligned Movement: Challenges and Way Forward - Kharel, Aswasthama Bhakta (Molung Educational Frontier, 2020)
Non-Aligned Movement commonly known as NAM has played a useful role in the common cause of World peace and prosperity. It has succeeded in steadily emerging as a central international forum. The newly independent nations of the world that have come into the one fold of this Movement have determined their own and resist the coercion of the World powers and their attempt to exploit them. During the cold war and in the present context, the Non-Aligned Movement examines its objectives and achievements in both periods. The main goals of NAM during block policy of more extraordinary powers, the structure of bipolar in international relations, the constant support and through its conferences and in the United Nations for World peaceful environment, détente, and disarmament, and prevention of the world into the block division (East and West). Despite these changes, several others new challenge that are arising, and its member states for the achievement of peace and security for humankind.